Dengue na região dos Vales do Taquari e Rio Pardo - RS? - Bavaresco, Flávia Pereira; Lara, Beanir Silva; Machado, Janete Aparecida Alves; Krummenauer, Eliane Carlosso; Carneiro, Marcelo (Revista de Epidemiologia e Controle de Infecção, 2012)
.